Diet‐induced obesity has a differential effect on adipose tissue and macrophage inflammatory responses of young and old mice1. (24th January 2013) - Wu, Dayong; Ren, Zhihong; Pae, Munkyong; Han, Sung Nim; Meydani, Simin Nikbin
Abstract Obesity and aging are both associated with increased inflammation in adipose tissue. In this study, we investigated effect of diet‐induced obesity on inflammatory status in young and old mice. Young (2 months) and old (19 months) C57BL/6 mice were fed a low‐fat (10%, LF) or high‐fat (60%, HF) diet for 4.5 months. Adipose tissue from old/LF mice expressed higher levels of IL‐1β, IL‐6, TNFα, and cyclooxygenase‐2 mRNA compared with young/LF mice. HF diet upregulated expression of all these inflammatory markers in young mice to the levels seen in the aged. Adipocytes, but not stromal vascular cells, from old/LF mice produced more IL‐6, TNFα, and prostaglandin (PG)E2 than those from young/LF mice. HF diet resulted in an increase of all these markers produced by adipocytes in young, but only TNFα in old mice. PGE2 produced by peritoneal macrophages (Mϕ's) was upregulated with aging, and HF diet induced more IL‐6, TNFα, and PGE2 production in young but not in old mice. Thus, HF diet/obesity induces an inflammatory state in both visceral fat cells and peritoneal Mϕ's of young mice, but not so in old mice. Together, these results suggest that HF diet‐induced obesity may speed up the aging process as characterized by inflammatory status. This study also indicates that animals have a differential response, depending on their ages, to HF diet‐induced obesity and inflammation. This age‐related difference in response to HF diet should be considered when using inflammation status as a marker in investigating adverse health impacts of HF diet and obesity. © 2013 BioFactors, 2013